Neuromuscular and motor strategies comparison among six different kicks executed by professional taekwondo players - Safaei, M. A.; Barnamehei, H. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
Introduction: Tae Kwon Do is the art of using hands and feet to defend what is now modern sports world has become [1]. It is very important for training plan that which muscles are more active in different kicks. Therefore, the current study aimed to analysis lower extremity muscle activities in different techniques, to find out relationship between muscle activities in different kicks to examine the effects of each muscle to improve training performance [2].